OPTIMIZATION SUSTAINED RELEASE TABLET FUCOIDAN PURIFIED EXTRACT FROM BROWN SEAWEED (Sargassum polycystum) AS IMMUNOMODULATOR - Ikasari, Endang Diyah; Wulansari, Endang Dwi; Purwanto, Ungsari Rizki Eka (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Fucoidan is a sulfate polysaccharide compound that is widespread in the sea, especially in brown algae. Previous fucoidan pharmacokinetics studies have shown that fucoidan nanoparticles have the effect of increasing the immunomodulatory ability of fucoidan, but fucoidan consumed orally has a half-life in plasma of about 3 hours so that to reduce the amount of fucoidan supplement use in a day, fucoidan can be formulated into sustained release tablet preparations. The purpose of this study was to determine the optimal composition of Na. Alginate and HPMC as polymers in sustained-release tablet preparations containing purified fucoidan from brown seaweed to produce tablets with characteristics that meet the compendial requirements of the Indonesian Pharmacopoeia and can maintain fucoidan release in plasma with only one consumption per day to improve user compliance. Fucoidan extraction from brown seaweed was carried out using hot extraction. Purified fucoidan tablets were prepared by the Simplex Lattice Design method using Design Expert version 10.1. The concentration of Na. Alginate and HPMC used as much as 2–5% with 8 formulas, which were then printed on a tablet printing tool. The optimum formula was tested as an immunomodulator in mice with parameters for lymph weight, phagocytosis index, and stimulant index. Optimum formula for Na. alginate: HPMC (3.252:3.748%) with flow speed 8.552 g/sec, compressibility 15,648%, hardness 3.726 kg, friability 0.044%, MC 3.296, Crushing time 21.34 minutes, Q15 34.608%, Q45 34.824%. The optimum formula for the immunomodulatory effect had a significant effect on the lymph weight of mice.